Can Masked Emotion-Laden Words Prime Emotion-Label Words? An ERP Test on the Mediated Account - Wu, Chenggang; Zhang, Juan; Yuan, Zhen (Frontiers in Psychology, 2021)
The present event-related potential (ERP) study explored whether masked emotion-laden words could facilitate emotion-label words and emotion-laden words processing in a valence judgment task. The results revealed that emotion-laden words as primes failed to influence target emotion-label word processing, whereas emotion-laden words facilitated target emotion-laden words in the congruent condition. Specifically, decreased late positivity complex (LPC) was elicited by emotion-laden words primed by the emotion-laden words of the same valence than those primed by the emotion-laden words of different valence. Nevertheless, no difference was observed for the emotion-label words as targets. These findings supported the mediated account that claimed emotion-laden words engendered emotion via the mediation of emotion-label words and hypothesized that emotion-laden words could not prime emotion-label words in the masked priming paradigm. Moreover, the present study provided additional evidence showing the distinction between the emotion-laden words and emotion-label words.